Navigating the Path to Viability: Lessons in Adaptation and Strategy from Si Sa Ket's Community Enterprises - Wannathong, Siriwuth (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2026)
This study examined the viability and sustainability of Community Enterprises (CEs) in the border areas of Si Sa Ket Province, Thailand, with particular attention to the operational, financial, governance, and market-related challenges that shaped their long-term survival. Using a qualitative multiple-case study design, data were collected from 60 key informants across selected Community Enterprise areas through semi-structured interviews, focus group discussions, participant observation, and document analysis. The participants included community leaders, local residents, Community Enterprise committee members, Community Enterprise members, and community committee members. Data were analyzed thematically to identify recurring patterns of challenge, adaptation, and strategic response. The findings revealed four major factors that influenced CE sustainability. First, external support strengthened initial capacity but also created dependency when it was supply-driven and short-term. Second, transparent and participatory governance was essential for building trust, accountability, and collective action. Third, market orientation was necessary for transforming local products and cultural resources into sustainable economic value. Fourth, intergenerational collaboration was critical for linking traditional knowledge with digital skills and future succession. Based on these findings, the study proposed a sustainability framework built on four core pillars: adaptive external support, participatory governance, market-oriented value creation, and intergenerational capability development. The study contributed practical insights for policymakers, development agencies, and community leaders seeking to strengthen rural Community Enterprises in peripheral borderland contexts.